Mirror foot: a case report of rare ten toes polydactyly - Sitorus, Gina Yunita J.; Putra, Teuku Nanda; Ikhsan, Muhammad; Jannah, Siti Miftahul (Surgical Residency Program Syiah Kuala University, 2023)
Introduction: A rare congenital deformity known as